AKTUALISASI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN MUTU SEKOLAH DI SMK NAHDLATUL ULAMA KOTA TASIKMALAYA - Salma Sania; Imas Komalasari; Upi Luthfiah Resnasari (Institut Nahdlatul Ulama Tasikmalaya, 2023)
An educational institution really needs leaders who can bring about change to improve the quality of the institution. To achieve this, leaders must have a style in their leadership, one of which is a transformational leadership style that school principals can apply to improve the quality of their institutions. This research aims to determine the actualization of transformational leadership in improving school quality at SMK Nahdlatul Ulama, Tasikmalaya City. This research uses a qualitative approach with data analysis techniques using three steps, namely data reduction, data display and data verification. The research results show that the application of transformational leadership consists of idealized influence by giving influence to subordinates to work together, individualized consideration by paying attention to subordinates' needs especially, inspirational motivation by providing motivation to subordinates in the form of rewards, and intellectual stimulation by increasing teacher competence such as through workshops. Meanwhile, the quality of education consists of: a) input, namely by recruiting human resources, providing facilities and infrastructure to support learning, financing, having an organization and job descriptions, making regulations, and making school plans, b) the process, namely by trying to provide services that are optimally for students through learning activities and school management, and c) output, which is seen from the scores of students who meet the KKM and the presence of students who achieve academic and non-academic achievements, and the absorption of graduates in the world of work reached 59%. Other achievements include becoming a school with a Center of Excellence (PK) program and becoming a Center of Excellence (COE) thereby increasing public interest and improving the brand image for the better.